2018
DOI: 10.1103/physreve.97.011202
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the equations of state in a relaxed magnetohydrodynamic plasma

Abstract: Measuring the equations of state in a relaxed magnetohydrodynamic plasma." Physical Review 97.1, 011202(R).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The goal of Swarthmore was to explore whether the helical Taylor state could become a suitable target for compression. Under this project, the team sought to measure the equations of state for a Taylor state by carrying out compression and heating experiments by creating a parcel of magnetized plasma, compressing it against the end wall of a chamber, and measuring plasma density, temperature, and magnetic field during compression [75], [76]. The team conducted their experiments on the existing Swarthmore Spheromak Experiment device (SSX), which has an advanced diagnostic suite and the capability to perform 100 experiments per day, which enabled rapid progress in understanding the behavior of these plasma plumes and illuminating their potential for use as new targets in the pursuit of fusion reactors.…”
Section: Exploratory Concepts Lawrence Berkeley National Laboratomentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of Swarthmore was to explore whether the helical Taylor state could become a suitable target for compression. Under this project, the team sought to measure the equations of state for a Taylor state by carrying out compression and heating experiments by creating a parcel of magnetized plasma, compressing it against the end wall of a chamber, and measuring plasma density, temperature, and magnetic field during compression [75], [76]. The team conducted their experiments on the existing Swarthmore Spheromak Experiment device (SSX), which has an advanced diagnostic suite and the capability to perform 100 experiments per day, which enabled rapid progress in understanding the behavior of these plasma plumes and illuminating their potential for use as new targets in the pursuit of fusion reactors.…”
Section: Exploratory Concepts Lawrence Berkeley National Laboratomentioning
confidence: 99%
“…In this work the team found that the parallel component of the Chew, Goldberger, and Low (CGL) equation of state was the best fit for the behavior of the Taylor state. [75] As a result, our understanding of the state of the art for Taylor state compression was advanced. The Swarthmore team observed that Taylor states have very different flux loss behavior than other targets, like field-reversed configurations, which may lead to significant flux decay when translating a Taylor State through a series of coils [77].…”
Section: Exploratory Concepts Lawrence Berkeley National Laboratomentioning
confidence: 99%
“…Over the past two decades, the Swarthmore Spheromak Experiment (SSX) has been used in many different configurations for the study of several interesting phenomena, such as magnetic reconnection [13] and self-organization [11,12], MHD turbulence [8], and magnetothermodynamics [14,15]. In the present configuration, the SSX device features a ∼ = 1.5 m-long high-vacuum chamber in which we generate n e ≥ 10 15 cm −3 , T i ≥ 20 eV, B ≤ 0.5 T hydrogen plasmas (See Figure 1).…”
Section: Ssx Devicementioning
confidence: 99%
“…In experiments using relaxed Taylor states [3][4][5][6], we accelerated and compressed magnetized plasmas while measuring local proton temperature T i , plasma density n e , and magnetic field B. A particular equation of state (EOS) was identified in these experiments [7,8].…”
Section: Introductionmentioning
confidence: 99%